Abstract P4-04-19: Recruitment of tumor associated macrophages in patients with breast cancer is not host dependent but tumor grade dependent - Ann Smeets; Giuseppe Floris; Kathleen Lambein; Sigrid Hatse; Annouschka Laenen; Ines Nevelsteen; Hans Wildiers; Marie-Rose Christiaens (Cancer Research, 2015)
Abstract Background: It has been shown that tumor related inflammation plays a crucial role in breast cancer progression. However, it remains unclear whether the density of immune cells in the tumor micro-environment is determined by tumour or by host characteristics. To answer this question, we measured tumor associated macrophage (TAM) density in 52 patients with a synchronous bilateral breast cancer with different lymph node status on both sites. Materials and methods: TAMs were identified by CD68 and CD163 antibodies. Tumour stromal macrophages were counted using a semi-quantitative method. GradeDescription0no TSMIscanty TSMIIsmall foci of TSMIIIlarge foci of TSMIVdiffuse dense infilatration of TSMTSM = tumor stromal macrophages Macrophage count was scored by two independent pathologists who were blinded from the clinicopathological data during the assessment. To evaluate the relative impact on TAM density exerted by the tumor itself and by the host, we used the likelihood ratio tests for the variance components related to host and tumor in determination of CD68 and CD163 levels. Results: In 60% of the tumors, the scores for CD68 and CD163 of both pathologists were identical resulting in a moderate concordance according to the weighted kappa coefficient te st (0.534; CI 0.418-0.649, p<0.0001). The TAM density strongly correlated with the number of mitosis and secondly with tumor grade. The results for CD68 and CD163 were similar. The association of clinicopathological variables with CD163 are shown. Association of clinicopathological variables with CD163VariableNScore (No(%))p-value0IIIIIIIVHistological subtype0.0883IDC1483 (2%)64 (43%)58 (39%)20 (14%)3 (2%)ILC310 (0%)21 (68%)7 (23%)3 (10%)0 (0%)Mixed80 (0%)0 (0%)7 (88%°1 (13%)0 (0%)Mitosis0.00050-101432 (1%)76 (53%)50 (35%)15 (10%)0 (0%)10-20191 (5%)9 (47%)7 (37%)1 (5%)1 (5%)>20250 (0%)0 (0%)15 (60%)8 (32%)2 (8%)Grade0.0226I450 (0%)22 (49%)19 (42%)4 (9%)0 (0%)II982 (2%)53 (54%)31 (32%)12 (12%)0 (0%)III441 (2%)10 (23%)22 (50%)8 (18%)3 (7%)pT0.23121931 (1%)49 (53%)32 (34%)10 (11%)1 (1%)2711 (1%)27 (38%)30 (42%)11 (15%)2 (3%)3211 (5%)9 (43%)10 (48%)1 (5%)0 (0%)420 (0%)0 (0%)0 (0%)2 (100%)0 (0%)pN0.13760922 (2%)44 (48%)39 (42%)6 (7%)1 (1%)+951 (1%)41 (43%)33 (35%)18 (19%)2 (2%)LVI0.8007No1623 (2%)73 (45%)64 (40%)19 (12%)3 (2%)Yes250 (0%)12 (48%)8 (32%)5 (20%)0 (0%)ER/Negative40 (0%)0 (0%)1 (25%)3 (75%)0 (0%)Positive1793 (2%)83 (46%)70 (39%)20 (11%)3 (2%)PR0.4849Negative250 (0%)10 (40%)10 (40%)5 (20%)0 (0%)Positive1563 (2%)73 (47%)60 (38%)17 (11%)3 (2%)Her-20.0903Negative1663 (2%)79 (47%)62 (37%)20 (12%)3 (2%)Positive80 (0%)0 (0%)6 (75%)2 (25%)0 (0%)Focality0.8170Unifocal11411 (1%)66 (47%)55 (39%)16 (11%)3 (2%)Multifocal462 (4%)19 (41%)17 (37%)8 (17%)0 (0%)Age at diagnosis0.8936<55601 (2%)18 (31%)35 (57%)6 (10%)0 (0%)55-65562 (4%)32 (57%)17 (30%)4 (7%)1 (2%)>65770 (0%)34 (44%)29 (38%)14 (18%)0 (0%) For both CD 68 and CD163, the tumor introduces important clustering or correlation, whereas the host does not introduce any additionale correlation. TAM recruitment is therefore primarily determined by tumor-related characteristics. Citation Format: Ann Smeets, Giuseppe Floris, Kathleen Lambein, Sigrid Hatse, Annouschka Laenen, Ines Nevelsteen, Hans Wildiers, Marie-Rose Christiaens. Recruitment of tumor associated macrophages in patients with breast cancer is not host dependent but tumor grade dependent [abstract]. In: Proceedings of the Thirty-Seventh Annual CTRC-AACR San Antonio Breast Cancer Symposium: 2014 Dec 9-13; San Antonio, TX. Philadelphia (PA): AACR; Cancer Res 2015;75(9 Suppl):Abstract nr P4-04-19.